Pranking News - Lemke, Donald B.; Spaziante, Patrick (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
Superman must stop the evil Mister Mxyzptlk from pulling off dangerous pranks throughout Metropolis.
At head of title: Superman.
Keywords: Adventure and adventurers -- Fiction; Superheroes -- Fiction; Good and evil -- Fiction; Superheroes -- Fiction; Supervillains -- Fiction; Good and evil -- Fiction; Adventure fiction